2021
DOI: 10.1016/j.stemcr.2021.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue stiffness triggers contractile dysfunction and telomere shortening in dystrophic cardiomyocytes

Abstract: Duchenne muscular dystrophy (DMD) is a rare X-linked recessive disease that is associated with severe progressive muscle degeneration culminating in death due to cardiorespiratory failure. We previously observed an unexpected proliferation-independent telomere shortening in cardiomyocytes of a DMD mouse model. Here, we provide mechanistic insights using human induced pluripotent stem cellderived cardiomyocytes (hiPSC-CMs). Using traction force microscopy, we show that DMD hiPSC-CMs exhibit deficits in force ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(76 citation statements)
references
References 48 publications
8
49
0
Order By: Relevance
“…Using a tuneable hydrogel and traction force microscopy, DMD cardiomyocytes were demonstrated unable to compensate for dystrophin deficiency when cultured on substrates with fibrotic-like elastic modulus (i.e. 35 kPa), showing impaired functionality while maintaining the features of DMD cardiomyopathy on 10 kPa hydrogels (Chang et al 2021 ). Different approaches aiming at understanding the triggers and mechanisms of cardiac pathologies rely on application of non-physiological stimuli to healthy cardiomyocytes.…”
Section: Pathology and Disease Modelsmentioning
confidence: 99%
“…Using a tuneable hydrogel and traction force microscopy, DMD cardiomyocytes were demonstrated unable to compensate for dystrophin deficiency when cultured on substrates with fibrotic-like elastic modulus (i.e. 35 kPa), showing impaired functionality while maintaining the features of DMD cardiomyopathy on 10 kPa hydrogels (Chang et al 2021 ). Different approaches aiming at understanding the triggers and mechanisms of cardiac pathologies rely on application of non-physiological stimuli to healthy cardiomyocytes.…”
Section: Pathology and Disease Modelsmentioning
confidence: 99%
“…This affects the microenvironment and possibly may contribute to increased substrate stiffness. Since increased substrate stiffness triggers contractile dysfunction associated with telomere shortening one may speculate that changes in the extracellular matrix environment by aged heart fibroblasts may support a phenotype of accelerated aging [105]. Moreover, studies demonstrated that aging of the heart is accompanied by disturbed expression patterns and distribution of Cx43, with age‐dependent decrease of Cx43 [106], which may be linked to increased risk for arrhythmic events [107].…”
Section: Communication Between Fibroblasts and Cardiomyocytesmentioning
confidence: 99%
“…The deposited TTR system is used again here with the addition of using the normal myocardium stiffness of 10 kPa so that the cells could shorten (Engler et al, 2008). A softer substrate avoids any dysfunctional changes due to higher stiffness (Chang et al, 2021). Stiffness is a major trigger of several mechanosignaling pathways making it a key factor in the regulation of muscle cell size (Russell & Solís, 2021; Solís & Russell, 2019).…”
Section: Discussionmentioning
confidence: 99%